How does a fraction get its name? - Powell, Arthur B. (Revista Brasileira de Educação em Ciências e Educação Matemática, 2019)
Abstract: Philosophical and cultural perspectives shape how a fraction is named and defined. In turn, these perspectives have consequences for learners’ conceptualization of fractions. We examine historical foundations of two perspectives of what are fractions—partitioning and measuring—and how these views influence fraction knowledge. For the dominant perspective, partitioning, we indicate how its approach to what is a fraction that discretizes objects and its well-meaning visual correlates cause learners a host of perceptual difficulties. Based on the human cultural and social practice of measuring continuous quantities, we then offer an alternative understanding of what is a fraction and illustrate the promise of this view for fraction knowledge. We introduce pedagogical tools, Cuisenaire rods, and illustrate how they can be used to implement a measuring perspective to comprehending properties and a definition of fractions. We end by sketching how to initiate a measuring perspective in a mathematics classroom. Keywors: Fractions; Gattegno; Measuring; Partitioning; Unit fractions. Como uma fração recebe seu nome? Resumo: Perspectivas filosóficas e culturais moldam como uma fração é nomeada e definida. Por sua vez, essas perspectivas têm consequências para a conceitualização de frações dos estudantes. Examinamos os fundamentos históricos de duas perspectivas do que são frações—particionamento e medição—e como essas visões influenciam o conhecimento das frações. Para a perspectiva dominante, partição, indicamos como sua abordagem ao que é uma fração que discretiza objetos e seu correlato visual bem-intencionado causa aos alunos uma série de dificuldades perceptivas. Com base na prática cultural e social humana de medir quantidades contínuas, oferecemos um entendimento alternativo do que é uma fração e ilustramos a promessa dessa visão para o conhecimento da fração. Introduzimos ferramentas pedagógicas, varas Cuisenaire e ilustramos como elas podem ser usadas para implementar uma perspectiva de medição para compreender propriedades e uma definição de frações. Terminamos esboçando como iniciar uma perspectiva de medição em uma sala de aula de matemática. Palavras-chave: Frações; Gattegno; Medição; Partição; Frações unitárias.